2018
DOI: 10.1007/s00253-018-9347-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil acidification amendments change the rhizosphere bacterial community of tobacco in a bacterial wilt affected field

Abstract: Application of soil amendments has been wildly used to increase soil pH and control bacterial wilt. However, little is known about causal shifts in the rhizosphere microbial community of crops, especially when the field naturally harbors the disease of bacterial wilt to tobacco for many years due to long-term continuous cropping and soil acidification. In this study, biochar (CP), lime (LM), oyster shell powder (OS) and no soil amendment additions (Control; CK) were assessed for their abilities to improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 59 publications
5
48
3
Order By: Relevance
“…At phylum level, Picual was always characterized by a higher relative abundance of Candidatus Saccharibacteria, both in the rhizosphere and the endosphere and in the structural (DNA) and the functional (RNA) communities, and in contrast to Frantoio plants that showed more abundance in Proteobacteria. Candidatus Saccharibacteria, formerly known as Candidate Division TM7, was recently suggested as a key biomarker in bacterial wilt disease suppression to indicate a state of malady and stress for the plant [34]. This study showed a negative correlation between the relative abundances of Candidatus Saccharibacteria and R. solanacearum in tobacco plants.…”
Section: Discussionmentioning
confidence: 62%
“…At phylum level, Picual was always characterized by a higher relative abundance of Candidatus Saccharibacteria, both in the rhizosphere and the endosphere and in the structural (DNA) and the functional (RNA) communities, and in contrast to Frantoio plants that showed more abundance in Proteobacteria. Candidatus Saccharibacteria, formerly known as Candidate Division TM7, was recently suggested as a key biomarker in bacterial wilt disease suppression to indicate a state of malady and stress for the plant [34]. This study showed a negative correlation between the relative abundances of Candidatus Saccharibacteria and R. solanacearum in tobacco plants.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have compared the microbial species abundance and diversity of bacterial wilt disease outbreak in soil samples [16][17][18]. Here, the microbial relative abundances and diversities of SS and CS were (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Pseudomonas also has a good inhibitory effect on RKNs (Siddiqui et al 2002). Notably, the analysis of soil microorganisms related to disease occurrence should target one or several specific types and be directed to the interaction among soil microbial communities (Shen et al 2018).…”
Section: Discussionmentioning
confidence: 99%